2007
DOI: 10.1002/ijc.22505
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and the risk of colorectal cancer: A prospective cohort study in Japan

Abstract: An inverse association between coffee consumption and the risk of colorectal cancer has been reported in several case-control studies, but results from prospective cohort studies have been inconclusive. We conducted a prospective cohort study among a Japanese population to clarify the association between coffee consumption and the risk of colorectal cancer incidence. We used data from the Miyagi Cohort Study for this analysis. Usable self-administered questionnaires about coffee consumption were returned from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 36 publications
2
48
1
Order By: Relevance
“…Five cohort studies (24,25,33,39,40) and nine case-control studies (26)(27)(28)(29)34,35,(41)(42)(43)) met the inclusion criteria. As regards cohort studies (Table 1 and Supplementary Table 1), all reported results for men and women separately (24,25,33,39,40); of these, one additionally reported results for men and women combined (33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five cohort studies (24,25,33,39,40) and nine case-control studies (26)(27)(28)(29)34,35,(41)(42)(43)) met the inclusion criteria. As regards cohort studies (Table 1 and Supplementary Table 1), all reported results for men and women separately (24,25,33,39,40); of these, one additionally reported results for men and women combined (33).…”
Section: Resultsmentioning
confidence: 99%
“…Two papers presented results on this issue using the same data source (32,33), one reporting incidence and another reporting mortality, and we used incidence data (33). After excluding two casecontrol studies that did not show 95% CI (34,35), we conducted a meta-analysis using random effects model (36) to estimate the summary RR/OR and 95% CI of colorectal cancer for the highest versus lowest category of coffee consumption.…”
Section: Methodsmentioning
confidence: 99%
“…In general, prospective cohort studies have found no significant associations with either proximal colon, distal colon or rectal cancer. [27][28][29][30][31][32] A recent meta-analysis of cohort studies only found a non-significant reduced colon cancer risk for high coffee consumers. 10 In contrast, a recent prospective cohort study (NIH-AARP Diet and Health study) showed a protective effect of coffee against proximal colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies provided negative conclusions for the effects of coffee consumption on human health. A large cohort study in Sweden and Japan indicated that coffee consumption was not associated with the risk of colorectal cancer [47,48]. Furthermore, another cohort study indicated that coffee consumption increased the risk of certain cancers, such as gastric cancer [49].…”
Section: Coffee and 8-oxo-gua / Ogg1mentioning
confidence: 99%